The optimisation, characterisation and platelet compatibility of polymeric nanocarriers loaded with NSAIDs - Crean, Joanne (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2014)
There is a constant drive towards improving global health by continuously enhancing the quality of drugs available and the systems to deliver these drugs efficiently in order to treat disease. This thesis focused on the development of two types of biodegradable polymeric nanocarriers (NCs), poly(lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) and hyaluronic acid:chitosan (HA:CS) polyelectrolyte complex nanoparticles (PECNs) loaded with two hydrophobic model drugs with anti-platelet action, indometacin (IND) and ketoprofen (KET). PLGA NPs were a hydrophobic system formed by an emulsion-solvent diffusion technique and HA:CS PECNs, which were hydrophilic systems formed based on electrostatic interactions between two polymers.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin